2011
DOI: 10.1371/journal.ppat.1002322
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 Is Critical in the Control of Chikungunya Virus Infection Independent of UbE1L Mediated Conjugation

Abstract: Chikungunya virus (CHIKV) is a re-emerging alphavirus that has caused significant disease in the Indian Ocean region since 2005. During this outbreak, in addition to fever, rash and arthritis, severe cases of CHIKV infection have been observed in infants. Challenging the notion that the innate immune response in infants is immature or defective, we demonstrate that both human infants and neonatal mice generate a robust type I interferon (IFN) response during CHIKV infection that contributes to, but is insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 63 publications
(101 reference statements)
2
170
3
Order By: Relevance
“…Among the ISGs analyzed, IRF7, RSAD2, ISG15, ISG54, ISG56, RIG-I, and PKR exhibited expression profiles similar to those of both IFNA and IFNB, which indicates that these ISGs are involved in the innate immune response against CHIKV. ISG15 was also recently shown to play a role in controlling CHIKV infection in mice (35). Notably, our data revealed that CHIKV viral load dictated the induction of IFNA, IFNB, IRF7, and RSAD2 during the acute phase.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Among the ISGs analyzed, IRF7, RSAD2, ISG15, ISG54, ISG56, RIG-I, and PKR exhibited expression profiles similar to those of both IFNA and IFNB, which indicates that these ISGs are involved in the innate immune response against CHIKV. ISG15 was also recently shown to play a role in controlling CHIKV infection in mice (35). Notably, our data revealed that CHIKV viral load dictated the induction of IFNA, IFNB, IRF7, and RSAD2 during the acute phase.…”
Section: Discussionsupporting
confidence: 58%
“…Despite extensive documentation about the induction of type I IFNs during CHIKV infection (22)(23)(24)34), only recently have the mechanisms of type I IFN control of CHIKV replication begun to be unraveled (24,25,35,41,50). However, the identities of ISGs that directly control and inhibit CHIKV replication still remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong innate immune responses, with high levels of type I IFN, proinflammatory cytokines, and chemokines, have been detected in acute CHIKV-infected patients (64)(65)(66)(82)(83)(84)(85)(86)(87)(88)(89)(90), nonhuman primates (91), and mice (62-64, 66, 92, 93) and might play a critical role in controlling virus replication. Although high levels of some proinflammatory cytokines have been associated with disease severity (82)(83)(84)(85)(87)(88)(89), type I IFN was identified as a key mediator responsible for viral clearance, and IFN-stimulated genes (ISGs) or IFN response factors 3 and 7 have been described to be critical in the control of CHIKV infection (63,64,66,90,94,95). Moreover, IFN-␣/␤ knockout mice (A129 mice) exhibited severe CHIKV disease (62-64, 66, 92), confirming the key role of type I IFNs in the control of CHIKV infection, by restricting virus replication early in the infection, although their effects are not enough to eliminate CHIKV from infected hosts.…”
Section: Discussionmentioning
confidence: 99%